Impacts of Diverse Workforce on Cyber Security and Information Technology Management - ALHEBSI, WADDAH SULTAN (2023)
The increasing dependence on digital technologies and the growing threat of cyberattacks made cybersecurity a critical concern for organizations worldwide. To address these challenges, organizations seek to develop diverse, skilled cybersecurity workforces that adapt to the constantly evolving threat landscape. However, little is known about the relationship between diversity in the cybersecurity workforce and performance, particularly in the context of the United Arab Emirates (UAE). The aim of thisresearch is to investigate the impacts and relationship of diverse workforce on the cyber security and information technology management through evaluation of role of mediating factors as identified in this research. The research objective sinclude, developing an understanding of diverse workforce, its importance and impacts on the global business industry. Identify major influencing factors of diversity which has impacts on efficiency of cyber security and information technology management and challenges within the cyber security and information technology management domains. Suggesting recommendations for improvements within cyber security and information technology management in terms of results and diversity factors to overcome challenges This study used a cross-sectional survey design to examine this relationship in the UAE. The sample included 51 organizations from three sectors (Government, Private, and Non-governmental) in the UAE. Results of a linear regression analysis and an analysis of variance (ANOVA) indicated that diversity in the cybersecurity workforce significantly impacts information technology management (CSITM) in the UAE. The research findings showed that this relationship has proved the diverse workforce has a positive and significant impact on cybersecurity and information technology management. These findings suggest that other factors may be more influential in determining Cyper Security Information Technology Managment in the UAE and that diversity may not be a key predictor of performance in this context. Despite these findings, organizations should continue to consider the potential benefits of diversity in the cybersecurity workforce, including improved decision-making, increased adaptability, enhanced creativity, greater representation, and improved team performance. To overcome the shortage of trained cybersecurity professionals and promote workforce diversity, organizations may need to adopt more flexible and inclusive work cultures and invest in training and development programs that support recruiting and retaining diverse team members. Further research is needed to more fully understand the relationship between diversity and performance in the context of cybersecurity and IT management in the UAE and other contexts.